Pengaruh Penggunaan Model Cooperative Learning Tipe Snowball Throwing Terhadap Keterampilan Sikap Sosial Siswa Pada Pembelajaran IPS Kelas III Sekolah Dasar - Nadiroti Muslihah, Neni (Pendidikan Guru Sekolah Dasar Institut Pendidikan Indonesia Garut, 2021)
IPS with floor plans and maps of the surrounding environment. After applying the cooperative learning model of the Snowball Throwing Type, the sample classes were students in class III-A as the experimental class and class III-B as the control class. The data collected from observations used observation sheets and questionnaire sheets. Collecting data from observations using the average formula, it is known that the students' teaching and learning process using the Snowball Throwing learning model, the results of the observations of students in the first meeting showed an average score of 69.5 students' skills. The second meeting was 72.9, and the third meeting was 81.2. Questionnaire data on student responses to learning using the Snowball Throwing Cooperative Learning model obtained data on the total score of the questionnaire score as a whole amounted to 2058 from 20 respondents with an average of 102.9 and the total percentage score of the overall questionnaire score was 16.4811 with an average of 82 based on on the criteria of Very Good.